A Randomized Clinical Case-Control Study On The Effects Of Ovulation Induction During Infertility Treatment On Gingival Inflammation - S, Visalini; P.K, Sasikumar; S, Santhosh; R, Dhivya; M, Nivethitha; Angel J, Jasmine (Journal of Neonatal Surgery, 2025)
Background: Exogenous sex hormones used in ovulation induction for infertility treatment may influence gingival health. This study evaluated changes in gingival inflammation among women receiving ovulation induction therapy. Methods: A 6-month case-control prospective parallel design study using purposive non-probability sampling was conducted on 49 women (20–35 years). Test groups received clomiphene citrate (CC) alone, CC+FSH, or CC+HMG. Controls received no induction drugs. Clinical indices—Plaque Index (PI), Gingival Index (GI), and modified Sulcus Bleeding Index (mSBI)—were recorded monthly. Statistical analysis included descriptive (frequency), inferential (mean, standard deviation, ANOVA) methods using SPSS v17.0. One-way ANOVA and post hoc tests were used for group comparisons. Results: GI and mSBI significantly increased in the test groups—especially in CC+HMG—compared to controls, despite similar PI scores (p < 0.05). Test Group I showed GI increases by months 1, 3, and 4, while Group III showed consistent GI and mSBI increases from months 3 to 6. Age and baseline PI, GI, and mSBI values showed no significant intergroup differences, indicating homogeneity at start. Conclusion: Ovulation induction, particularly CC+HMG, significantly aggravates gingival inflammation. Periodontal monitoring is essential during infertility treatment.